Measurement of the social investment impact of the bahtera segara program using the social return on investment method (SROI) - Asmoro, Aryo Aji; Nurwafi F, Luthfi; Shintadewi, Milasania (ARKA INSTITUTE, 2024)
PT Pertamina Patra Niaga Integrated Terminal Semarang conducted this study to analyze the impact of the BAHTERA SEGARA (Bahagia Sejahtera Nelayan Pesisir Semarang Utara) Program, aiming to enhance the program's quality in the future. This research employs the SROI method to measure the impact of all activities carried out by PT Pertamina Patra Niaga Integrated Terminal Semarang within the framework of the BAHTERA SEGARA (Bahagia Sejahtera Nelayan Pesisir Pesisir Semarang Utara) Program. Based on the study results of the BAHTERA SEGARA Program (Bahagia Sejahtera Nelayan Pesisir Semarang Utara), this program has proven to be effective and has a significant positive impact. The program has succeeded in improving the economic, social, and environmental welfare of the target community groups and communities that replicate it independently. Increasing SROI scores from 2020 to 2023 indicate that the program is increasingly effective in delivering benefits, particularly through the replication of food crop cultivation and increased fish processing productivity. The program also contributes to the reduction of greenhouse gas emissions and supports climate change adaptation efforts. The program's successful replication demonstrates the effectiveness of BAHTERA SEGARA as a collective learning tool, as well as its potential for replication in other areas with similar conditions.